The heart of desire keys to the pleasures of love - Resnick, Stella 1939- (Hoboken, N.J Wiley, 2012)
"Fresh approach to solving the love/lust dilemma--the concept that love can actually kill libido. Drawing on author's decades of work with her clients, this breakthrough book shows how couples can bring the passion back to their long-term relationships Author has strong media experience and ongoing media contacts and gives lectures across the country"--
"In The Heart of Desire, Stella Resnick reveals that love and desire are opposing forces and demonstrates how to override our hard-wired instincts in order to experience long-term relationships that are both emotionally and sexually gratifying. ContentsAcknowledgmentsIntroductionPART I: LOVE AND ROMANCEChapter 1: The Love-Lust DilemmaChapter 2: What Dampens DesireChapter 3: Love, Sex, and StressChapter 4: Romance and DesireChapter 5: Body TalkPART II: SEXUAL PLEASUREChapter 6: Sexual Health and the BodyChapter 7: The Evolving OrgasmChapter 8: Nuances of Sexual PleasureChapter 9: Ultimate PleasuresChapter 10: Desire for Life "--
Includes bibliographical references and index
1
Keywords: Desire; FAMILY & RELATIONSHIPS / Family Relationships; Love; Sex (Psychology)